(untitled) (Journal of Academic Research, 2020)
The aim of this study is to demonstrate the significances of neck circumference (NC) and Body Mass Index (BMI) in obstructive sleep apnea (OSA) based on age groups. The influence of OSA diagnosed according to age groups was discussed. The study was done in Misurata city for 243 (135 males and 108 females aged 13-80yrs) patients referred to the Misurata city sleep clinic with suspected OSA. Polysomnography (PSG) was done for all. The main finding in this study was that the mean of BMI in age group (45-55yrs) was higher in females and the mean of NC was higher in males for all age groups. Simple linear regression analysis showed that there was significant positive correlation between BMI and respiratory disturbance index (RDI) in addition there was also positive significant correlation between NC and RDI specifically in middle and elder age groups (35-45yrs), (55-65yrs) respectively. Furthermore, using multiple linear regression analysis for both BMI and NC it was found that the NC was the only significant associated with RDI in middle and elder age groups. In addition, it was demonstrated that NC could be more associated with OSA than BMI in middle and elder Misurata patients.